Updates and Advances in Nephrolithiasis Pathophysiology, Genetics, and Treatment Modalities - Long, Layron (IntechOpen, 2017)
In recent decades, we have enhanced our understanding of the pathophysiology and genetics of rare and common causes of kidney stones. With our evolving understanding of the epidemiology, biology, and genetics of nephrolithiasis and the advances in therapeutic technologies, we have made significant progress in patient care. Furthermore, advances in the medical management and surgical technologies have allowed us to embellish the optimal outcomes in the management of complex kidney stone disease.